Art as inspiration in interior space - KOÇ SAĞLAM, CEREN; GÖKER PAKTAŞ, MÜGE (My University, 2023)
Space, which is a multi-layered and dynamic concept, has been attempted to be understand by human beings as a physical reality that defines the space we live in, such as boundary, place or space. For the early humans, while meeting the needs of shelter as a space, they also expressed themselves by describing their lives with the pictures they drew on the cave surfaces. These descriptions have been accepted as the most primitive artistic expressions. Developing and changing opportunities in time have found various representation areas such as philosophy, literature and architecture at the intersection of art and space. The aim of this study is to examine the architectural production environment and interdisciplinary interactions we are in through the mutual relationship it establishes with art. The main question of the research focuses on how art can enable an alternative approach to the contemporary conception of space as inspiration. It is aimed to understand the dynamics of the interaction environment based on the inspiration of art for different disciplines, to reveal the ties, opportunities and potentials for the current situation and the future in the light of examples. Regardless of the definition of space adopted, producing and sharing art-inspired expressions will contribute to the establishment of an alternative framework in the interior. For this reason, the concept of space necessitates the existence of this discussion in the context of its relationship with art.
Keywords: Art; Space; Inspiration